Hydrogels for Medical and Environmental Applications. Issue 3 (13th January 2020) - Jayakumar, Anjali; Jose, Vishal K.; Lee, Jong‐Min
Abstract: Hydrogels are heavily‐hydrated 3D microliths having loose, porous structures. Unlike organogels, elastomers, and carbohydrates, hydrogels are structures with water as a continuous phase/solvent. Being water‐based, they provide a lot of scope for facile improvizations in their structure and in introducing chemical functionalities. They can house various functional materials in their highly porous networks, making them potential candidates for diverse applications. Various possibilities in using different starting materials for hydrogels are described herein, and it is shown how choosing and optimizing these components that make up the hydrogel can modify their properties. Studying hydrogels and their formulations will enable the understanding of their multifunctional properties. External stimuli‐responsive and functional systems can be designed out of these microliths to suit a wide range of applications like biosensing, cancer therapy, regenerative medicine, drug delivery, environmental parameter sensing, water desalination, heavy‐metal adsorption, and water treatment. Environmental degradation is occurring at an alarming rate, cascading the adverse effects on the environment but also causing detrimental effects in public health. In this review, multiple perspectives from state‐of‐the‐art literature are brought together to examine hydrogels as very powerful, sustainable, cost‐effective, and simple solutions for the betterment of the environment and subsequently, public health. Abstract : Recent works in the field of hydrogels are reviewed, which hold great promise in addressing urgent challenges in the field of healthcare and environmental pollution mitigation. Hydrogels are water‐filled, 3D monoliths, which can house various functional materials in their porous frameworks. This review comprehensively describes how they are extensively researched for use in a variety of applications.